SUPPLY, DEMAND AND ELASTICITY OF FISH - Babović, Jovan; Ignjatijević, Svetlana; Đorđević, Dragomir (Economics of Agriculture, 2011)
We studied the factors that determine supply, demand and elasticity of consumption of fish in the world, EU and Serbia. The annual fish supply in the world is 145 million tons with a rate increase of 1.9%. World production per capita is 21.3 kg and the consumption is 17.2 kg. Production in the EU amounts to 12 million tons of fish and participates in the world`s production with 8.3%. Consumption per capita has stagnated at 22 kg. Fish production in Serbia is 12.5 thousand tons and records an increase rate of 20%. Production per capita is 1.7 kg, and the consumption is 5.7 kg. The income elasticity of consumption of fish in the EU is inelastic and is 0.423, and -0.311 in price. In Serbia, income elasticity of fish consumption is 0.549, and -0.402 in price. The elasticity of fish consumption compared to the prices of pork and chicken meat is positive, low and shows that these meat are substitutes. Regression parameters show that an increase in income causes a greater demand for fish, and increase in prices of fish has influenced decreased demand.